2021
DOI: 10.1111/ctr.14293
|View full text |Cite
|
Sign up to set email alerts
|

Renal function outcomes and kidney biopsy features of living kidney donors with hypertension

Abstract: Background The medium‐ to long‐term outcomes of living kidney donors with hypertension compared to normotensive donors are not well understood, especially with the recent changes in hypertension guidelines. Methods We studied a cohort of 950 living kidney donors using different definitions of hypertension based on either ≥140/90 or ≥130/80 mmHg thresholds and based on either office or ambulatory blood pressure readings. Microstructural features on kidney biopsy at the time of donation were compared using diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…As reported previously, self-reported data have been validated when compared to objective in available medical records. 17 , 23 The survey was not designed to assess for stone recurrence and not all SFs had medical records for review, thus stone recurrence during follow-up was not assessed.…”
Section: Methodsmentioning
confidence: 99%
“…As reported previously, self-reported data have been validated when compared to objective in available medical records. 17 , 23 The survey was not designed to assess for stone recurrence and not all SFs had medical records for review, thus stone recurrence during follow-up was not assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Merzkani et al found that, among 950 donors, those with controlled hypertension had larger glomeruli and arteriolar hyalinosis in implantation biopsies, but did not have significantly lower GFR 10 years post-donation. However, high office blood pressure and non-dipping status were associated with higher risk of proteinuria [ 25 ]. Fahmy et al followed 310 donors who underwent an implantation protocol biopsy for a median of 6.2 years.…”
Section: Discussionmentioning
confidence: 99%